ChemInform Abstract: Efficient One Pot Multi‐Component Domino Aldol Condensation—Michael Addition—Suzuki Coupling Reaction for the Highly Functionalized Quinolines. Issue 47 (November 2015) - Ubba, Eethamukkala; Kumar, Y. Suneel; Dasaradhan, C.; Khan, Fazlur‐Rahman Nawaz; Jeong, Euh Duck; Chung, Eun Hyuk
Abstract: The title sequence allows the synthesis of highly functionalized quinolines via three‐ component reaction of 2‐chloro‐3‐formylquinolines, acetophenones, and boronic acids.